Client values within post-disaster reconstruction contracting services. Issue 3 (5th June 2017) - Aliakbarlou, Sadegh; Wilkinson, Suzanne; Costello, Seosamh B.; Jang, Hyounseung
Abstract : Purpose: The purpose of this paper is to explore and prioritize the key client values within contracting services for reconstructing the built environment in post-disaster situations. Design/methodology/approach: A literature review, semi-structured interviews and questionnaire survey were included in this study. A comparative analysis was used to obtain different perspectives between public and private sectors. Findings: A total of 39 client values were identified in this study. Clients for disaster reconstruction services put more emphasis on values such as timeliness, availability of resources, competency, building a trust-based relationship, financial stability, and communication techniques than contract price. Public and private clients have a different perspective regarding the importance of the identified values, while these are not statistically significant for the most important values. Research limitations/implications: The construction literature is focussed on business-as-usual rather than post-disaster reconstruction. To ensure that reconstruction programmes after a disaster are successfully implemented, it is necessary to identify and prioritize the client values within contracting services. Focussing the attention of the service providers on these values is believed to have the greatest impact on the programmes' success. Practical implications: Understanding the client values identified by this study can aid contractors to better prepare for reconstruction programmes and provide improved services to clients. Originality/value: A number of important client values within contracting services that appear to have a bearing on the success of disaster reconstruction programmes were identified in this study.